Peliosis Hepatis following treatment with androgen-steroids in patients with bone marrow failure syndromes - P. Tsirigotis; T. Sella; M.Y. Shapira; M. Bitan; A. Bloom; D. Kiselgoff; M. Levin; D. Libster; A. Abdul Hai; B. Gesundheit; R. Or; S. Slavin; et al. (Haematologica, 2007)
Androgens widely used in the treatment of bone marrow failure syndromes can in rare cases cause hepatic peliosis, a pathological entity characterized by multiple blood-filled cavities in the liver parenchyma. Bone marrow failure syndromes per se are associated with a low coagulation status, which is further magnified by bone marrow transplantation for aplastic anaemia due to deep thrombocytopenia. Both these conditions can cause bleeding; their combination is especially dangerous. We describe two cases of aplastic anaemia due to paroxysmal nocturnal hemoglobinuria and Fanconi syndrome, in which patients developed peliosis hepatis after prolonged treatment with androgens. One patient developed severe subcapsular bleeding, successfully treated with catheterization of the right hepatic artery and embolization of the bleeding site. The second patient bridged over deep post-transplant aplasia with high frequency platelet transfusions, and demonstrated an uncomplicated post-BMT course. We suggest avoiding or interrupting treatment with androgens in patients preparing for BMT.